SLOPE STABILITY ANALYSIS USING GEOELECTRIC IN ROAD DUAPITUE DISTRICT, SIDRAP REGENCY - sudarwin kamur (Geographica: Science and Education Journal, 2019)
Research has been carried out on lanslide slip area of landslide of the road in Duapitue Sidrap. This study aims to determine the slip field using geoelectricity which is suspected as the cause of slope stability/landslide disturbance in terms of resistivity values in each layer and to determine the structure and coating of subsurface soils in the Kampale sub-village, DuaPitue. Information about the structure and coating of the land is used to determine the limits of soil instability that can be used as a reference in the planning of cliff/ slope strengthening on the intended road. From the cross section of the material resistivity, it can be seen that the weak zones on the shoulder and the road body are more than 10 meters deepth. Most of the overburden is unconsolidated fill material, covered by alluvium material with a fairly large air composition with a thickness of 5-10 meters. Slip area of lanslide formed at an average depth of 12 meters between the weak zone of the embankment material layer and the water-saturated alluvium layer with relatively solid alluvium and sandstone material beneath it.